2006
DOI: 10.1016/j.physa.2005.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Zipf law for Brazilian cities

Abstract: This work studies the Zipf Law for cities in Brazil. Data from censuses of 1970, 1980, 1991 and 2000 were used to select a sample containing only cities with 30,000 inhabitants or more. The results show that the population distribution in Brazilian cities does follow a power law similar to the ones found in other countries. Estimates of the power law exponent were found to be 2.22 ± 0.34 for the 1970 and 1980 censuses, and 2.26 ± 0.11 for censuses of 1991 and 2000. More accurate results were obtained with th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 4 publications
0
30
0
1
Order By: Relevance
“…Nitsch also enumerated some factors influencing the variation of ã exponents, such as the base population (metropolitan areas or inner cities), the country (USA, Japan, China), and the small number of observations. Moura and Ribeiro [73] studied Brazilian cities with more than 30,000 inhabitants. They showed that Pareto distribution was not valid for smaller cities.…”
Section: Power Laws For Citiesmentioning
confidence: 99%
“…Nitsch also enumerated some factors influencing the variation of ã exponents, such as the base population (metropolitan areas or inner cities), the country (USA, Japan, China), and the small number of observations. Moura and Ribeiro [73] studied Brazilian cities with more than 30,000 inhabitants. They showed that Pareto distribution was not valid for smaller cities.…”
Section: Power Laws For Citiesmentioning
confidence: 99%
“…In reality, individual cities undergo turbulent fluctuations in size and rank within the city system, even if the system remains a stable distribution at the aggregated level (Batty, 2006a(Batty, , 2010Black & Henderson, 2003;Guerin-Pace, 1995;Nitsch, 2005;Parr, 1985;White, Kejzar, Tsallis, & Rozenblat, 2005). Third, the influencing factors of citysize distribution in developing countries, especially institutional forces, are distinctive from those in developed countries (Krakover, 1998;Moura & Ribeiro, 2006;Soo, 2007). However, few studies have been conducted in developing countries, and even fewer have discussed the situation after 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Imagine we have a forest with some percolations (Reynolds, et. al., 1977) among them which somewhat is also showing the size of "population" distribution that also emerging the power law (Moura, 2006). A lightning strikes and ignites a fire on one particular tree.…”
Section: R =mentioning
confidence: 80%